Syngas production by electrocatalytic reduction of CO2 using Ag-decorated TiO2 nanotubes. (9th October 2020) - Farkhondehfal, M.A.; Hernández, S.; Rattalino, M.; Makkee, M.; Lamberti, A.; Chiodoni, A.; Bejtka, K.; Sacco, A.; Pirri, F.C.; Russo, N.
Abstract: Huge efforts have been done in the last years on electrochemical and photoelectrochemical reduction of CO2 to offer a sustainable route to recycle CO2 . A promising route is to electrochemically reduce CO2 into CO which, by combination with hydrogen, can be used as a feedstock to different added-value products or fuels. Herein, perpendicular oriented TiO2 nanotubes (NTs) on the electrode plate were grown by anodic oxidation of titanium substrate and then decorated by a low loading of silver nanoparticles deposited by sputtering ( i.e. Ag/TiO2 NTs). Due to their quasi one-dimensional arrangement, TiO2 NTs are able to provide higher surface area for Ag adhesion and superior electron transport properties than other Ti substrates ( e.g . Ti foil and TiO2 nanoparticles), as confirmed by electrochemical (CV, EIS, electrochemical active surface area) and chemical/morphological analysis (FESEM, TEM, EDS). These characteristics together with the role of the TiO2 NTs to enhance the stability of CO2 ·- intermediate formed due to titania redox couple (Ti IV /Ti III ) lead to an improvement of the CO production in the Ag/TiO2 NTs electrodes. Particular attention has been devoted to reduce the loading of noble metal in the electrode(14.5 %w/%w) and to increase the catalysts active surface area in order to decrease the required overpotential. Graphical abstract: Image 1 Highlights: Ag NPs has been sputtered over Titania nanotubes to be used as electrocatalyst. Higher amount of Ag can not necessarily increase the activity of electrocatalyst. Increasing the pressure can result in higher production of CO in low potentials. Titania nanotube used as a support for Ag to increase its active surface area. Titania can help to stabilize intermediate radicals of CO2 reduction to CO.